2022
DOI: 10.1155/2022/5463505
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MDRL Mitigates Atherosclerosis through miR-361/SQSTM1/NLRP3 Signaling

Abstract: Objective. Long non-coding RNAs (lncRNAs) play many important roles in gene regulation and disease pathogenesis. Here, we sought to determine that mitochondrial dynamic related lncRNA (MDRL) modulates NLRP3 inflammasome activation and apoptosis of vascular smooth muscle cells (VSMCs) and protects arteries against atherosclerosis. Methods. In vivo experiments, we applied LDLR knockout (LDLR-/-) mice fed the high-fat diet to investigate the effects of MDRL on atherosclerosis. In vitro experiments, we applied mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…Lin et al reported the association between mitochondrial dynamic-related lncRNA (MDRL) and atherosclerosis in VSMCs [55]. They first demonstrated that MDRL is downregulated in atherosclerotic plaques, and overexpression of MDRL ameliorated the burden of plaques in the aortic roots of low-density lipoprotein receptor knockout (LDLR −/− ) mice.…”
Section: Atherosclerosismentioning
confidence: 99%
“…Lin et al reported the association between mitochondrial dynamic-related lncRNA (MDRL) and atherosclerosis in VSMCs [55]. They first demonstrated that MDRL is downregulated in atherosclerotic plaques, and overexpression of MDRL ameliorated the burden of plaques in the aortic roots of low-density lipoprotein receptor knockout (LDLR −/− ) mice.…”
Section: Atherosclerosismentioning
confidence: 99%
“…Atherosclerosis (AS) is a chronic inflammatory artery disease that has emerged as a major public health concern around the world [ 1 , 2 ]. Endothelial cell dysfunction is defined by increased inflammatory gene expression or decreased diastolic and contractile function [ 3 ], whereas endothelial cell activation is characterized by increased inflammatory gene expression and permeability, both of which are thought to be major causes of AS [ 4 ].…”
Section: Introductionmentioning
confidence: 99%